A Analisis Hubungan Kebiasaan Merokok dengan Hipertensi di Kuok Kabupaten Kampar - Apriza Apriza; Muhammad Nurman (LPPM Hang Tuah Pekanbaru, 2022)
Hypertension is known as the most worrying disease and has a high risk of death and is known as the silent killer. The increase in the total number of cases of hypertension is mostly caused by lifestyle factors. Smoking is a lifestyle that can be controlled, it takes ten seconds for nicotine to reach the brain. This study aims to analyze the relationship between smoking and hypertension in the Technical Implementation Unit (UPT) of the Regional Public Service Agency (BLUD) Kuok Health Center, Kampar Regency in 2021. The study was conducted using a cross-sectional method. The study population was patients who visited for treatment at UPT BLUD Puskesmas Kuok, sampling was done by purposive sampling technique. The sample consisted of 75 patients who visited the adult polyclinic for treatment. The research instrument was a checklist sheet and a questionnaire about smoking habits and hypertension. Research data shows that the number of hypertension sufferers who smoke reaches 52 people or 83.9%. The significance value (p-value) of the relationship between hypertension and smoking habits is 0.003 indicating that there is a relationship between smoking habits and hypertension. The OR value is 6.067, which means that the risk of hypertension is 6.067 times higher for smokers than non-smokers.